Paget's disease of bone: an update on epidemiology, pathogenesis and pharmacotherapy. (3rd August 2018) - Gennari, Luigi; Rendina, Domenico; Picchioni, Tommaso; Bianciardi, Simone; Materozzi, Maria; Nuti, Ranuccio; Merlotti, Daniela
ABSTRACT: Introduction : Paget's disease of bone (PDB) is a chronic bone disorder, which affects middle-aged or older adults and results in enlarged and deformed bones in one or more skeletal regions. Family history has been reported in up to 40% of cases, suggesting a consistent genetic predisposition . At affected sites, the characteristic feature of PDB is an increased resorption followed by an increased bone formation, producing a disorganized and structurally abnormal bone. Consequently, bone pain, arthritis, deformities, and fractures can occur. In less than 1%, neoplastic degeneration in osteosarcoma, or giant cell tumor has been described at PDB sites. Areas covered : We provide a contemporary overview of the epidemiology, pathogenesis and treatment of PDB. Expert opinion : While recent epidemiological evidence indicates a decreasing prevalence and severity of PDB, over the past two decades there have been consistent advances on the genetic mechanisms of PDB. It is now clear that PDB is a genetically heterogeneous disorder, with at least three different genes ( SQSTM1, ZNF687, FKBP5 ) involved in the classic form and four additional genes identified in PDB-related syndromes. The clinical management of PDB has also evolved, with the development of the most potent aminobisphosphonate, zoledronic acid, which allows long-term remission in the majority of patients.